Efficacy of a nutrition education intervention designed to improve overall diet quality of female adults - Khan, Hira (Progress in Nutrition, 2018)
Objective: Determine the effectiveness of a nutrition education (NE) intervention in improving nutritional knowledge and diet quality. Design: Quasi experimental with a control group. Setting/Participants/Intervention: Fifty six female undergraduate students aged 18-24 years. The experimental group (n=28) received 44 sessions of NE lectures while the control group (n=28) received no intervention. Main Outcome Measures: Questionnaire with nutrition knowledge questions, semi-quantitative FFQ distributed at pre-test, posttest (3M) and posttest 2 (6M). USDA food composition tables were utilized to calculate a Diet Quality Index-International (DQI-I) score. Analyses: Analysis through SPPS with significance at p